DEBAT KETIGA: Memikirkan Kembali Keilmuan Hubungan Internasional - Kristianti, Aryani; Maliki, Musa (Global: Jurnal Politik Internasional, 2007)
This article will argue that Third Debate is the 'revolution turn' in the study of international relations. There are some explanations to conduct this argument: the description of the history of international relations thought and epistemological problem. This illustration will lead us to understand that there is a deeply dynamic debate in philosophy circumstances. We can not close the eyes to this debate otherwise we will be stucked and trapped in the dogmatism, stagnatism and ideology. Epistemological problem of philosophy is one of the foundations of the entire big problem that should be discussed. From epistemological scrutiny, this article believes in Smith illustration that the variety of epistemological types will solve the problem of dog matism, stagnatism and ideology in the study of international relations. This 'revolutions turn' will achieve variety of truth, a wisdom, and a freedom from (of) dogmatism, stagnatism and ideology in the study of inter national relations.